2008
DOI: 10.1128/jvi.00141-08
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Is Critical for the Clearance of Murine Norovirus Infection

Abstract: Human noroviruses cause more than 90% of epidemic nonbacterial gastroenteritis. However, the role of B cells and antibody in the immune response to noroviruses is unclear. Previous studies have demonstrated that human norovirus specific antibody levels increase upon infection, but they may not be protective against infection. In this report, we used murine norovirus ( Extensive studies have demonstrated that humoral immune responses are generated by challenge with various norovirus strains in humans, pigs, cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
80
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 57 publications
3
80
1
Order By: Relevance
“…Both hypotheses are supported by the finding from this study that daily viral RNA titre is associated with multiple proinflammatory serum cytokines and chemokines. The immune response to NoV has been found to be critical for limiting viral replication and eventually clearing infection [27,34,35]. However, there may also be immune-mediated damage, as seen in other enteric infections [36].…”
Section: Discussionmentioning
confidence: 99%
“…Both hypotheses are supported by the finding from this study that daily viral RNA titre is associated with multiple proinflammatory serum cytokines and chemokines. The immune response to NoV has been found to be critical for limiting viral replication and eventually clearing infection [27,34,35]. However, there may also be immune-mediated damage, as seen in other enteric infections [36].…”
Section: Discussionmentioning
confidence: 99%
“…Chachu et al have shown that virus levels in persistently infected Rag1 Ϫ/Ϫ mice can be reduced by adoptive transfer of total splenocytes from CW3 immune donors. Furthermore, viral control in these studies required the presence of all three components of the adaptive response, i.e., B cells and CD4 and CD8 T cells, as selective depletion of any one of these subsets prior to transfer led to incomplete viral clearance (49,50). The relative importance of specific B or T cell subsets individually to MNV clearance, however, has not been examined.…”
Section: Fig 4 Epitope P1mentioning
confidence: 99%
“…Thus, Rag1 Ϫ/Ϫ mice fail to clear MNV-CW3, while immunocompetent mice clear this same strain within 7 days. In addition, selective depletion of CD4 T cells, CD8 T cells, or B cells from wild-type mice impairs MNV clearance and leads to higher viral titers in the intestine and mesenteric lymph nodes (MLN) (49,50). Furthermore, adoptive transfer of splenocytes from MNV immune wildtype mice was sufficient to clear the same strain from chronically infected Rag1 Ϫ/Ϫ recipients (49).…”
mentioning
confidence: 99%
“…MNV has also been isolated from wild mice, confirming its widespread distribution (59). Studies with MNV have begun to probe various aspects of the norovirus replication cycle, including entry mechanisms and attachment factors (24,48,49,67), viral protein function (8,19,30,43,64,66), determinants of virulence (7), and host immune responses (14,15,42); however, our understanding of the molecular mechanisms of norovirus genome translation and replication lags far behind that for other RNA viruses.…”
mentioning
confidence: 99%